2021
DOI: 10.1111/tri.13957
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value and limitations of the preoperative C‐reactive‐protein‐to‐albumin ratio in predicting post‐operative morbidity and mortality after deceased‐donor liver transplantation: a retrospective single‐centre study

Abstract: Summary Liver transplantation is still associated with a high risk of severe complications and post‐operative mortality. This study examines the predictive value of the preoperative C‐reactive‐protein‐to‐albumin ratio (CAR) regarding perioperative morbidity and mortality in deceased‐donor liver transplantation (DDLT) recipients. In total, 390 DDLT recipients between 05/2010 and 03/2020 were eligible. Predictive abilities of CAR were examined through receiver operating characteristic curve (ROC) analyses. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…Moreover, Amygdalos and his colleagues studied 390 LT recipients and demonstrated that preoperative proteinuria is a reliable tool to predict mortality in LT recipients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Amygdalos and his colleagues studied 390 LT recipients and demonstrated that preoperative proteinuria is a reliable tool to predict mortality in LT recipients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence from previous studies suggests that the CAR is a reliable prognosticator of outcome and indicator of patient status [7,8,[12][13][14][15][16]. Specifically, among patients undergoing LT with prevalent concomitant immune dysregulation [20], a higher CAR is reported to be associated with poorer liver cirrhosis prognosis and higher early allograft dysfunction following LT [14].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response of the host in the tumor microenvironment is known to play a crucial role in cancer growth and progression and is further linked to systemic inflammation [ 5 ]. In this context, counts of neutrophils, lymphocytes, and platelets, as well as hypoalbuminemia and high C-reactive protein (CRP) levels have all been used to calculate clinical scores or ratios, such as the Glasgow Prognostic Score (GPS), the platelet-to-lymphocyte ratio (PLR), and the neutrophil-to-lymphocyte ratio (NLR), which have shown associations with oncological and surgical outcomes in various solid tumors [ 6 , 7 , 8 , 9 ]. However, there are conflicting results regarding these preoperative systemic inflammatory parameters in CCA [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%